2014
DOI: 10.2214/ajr.14.12849
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in Shoulder MRI: Part 2—Biceps Tendon, Bursae and Cysts, Incidental and Postsurgical Findings, and Artifacts

Abstract: Imaging pitfalls in and around the shoulder are not limited to normal anatomy and anatomic variants. Radiologists must be cognizant of the vast variability of structures in the shoulder and of the incidental and postsurgical findings and artifacts affecting them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Contrast can be seen in the superior subscapular recess as these as communicate with the joint in 47.5% of cases [9]. Contrast is most commonly seen in the subacromial/subdeltoid space following a full thickness rotator cuff tear [10]. The subacromial/subdeltoid space communicates with the subcoracoid bursa in 11-55% of cases [11].…”
Section: Discussion Clinical and Imaging Findingmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrast can be seen in the superior subscapular recess as these as communicate with the joint in 47.5% of cases [9]. Contrast is most commonly seen in the subacromial/subdeltoid space following a full thickness rotator cuff tear [10]. The subacromial/subdeltoid space communicates with the subcoracoid bursa in 11-55% of cases [11].…”
Section: Discussion Clinical and Imaging Findingmentioning
confidence: 99%
“…The subacromial/subdeltoid space communicates with the subcoracoid bursa in 11-55% of cases [11]. Following a rotator cuff tear and inferior acromioclavicular ligament tear, contrast may extend superior to the acromioclavicular joint giving the characteristic 'geyser sign' [10]. Subscapularis muscle and tendon injection is not uncommon [7].…”
Section: Discussion Clinical and Imaging Findingmentioning
confidence: 99%
“…This is known as the geyser sign and masses can result, either above the AC joint or into the adjacent muscle ( Figure 21 ). If large enough, these masses may mimic a tumour on clinical assessment [ 87 ]. MRI can be an important diagnostic tool in these instances, and allow for concomitant evaluation of the AC joint, glenohumeral joint, and rotator cuff pathology [ 88 , 89 ].…”
Section: Acromioclavicular Jointmentioning
confidence: 99%
“…The vacuum phenomenon is currently defined as the accumulation of air in natural cavities such as synovial joints and intervertebral discs (Jordanov and Block, 2010 ; D'Anastasi et al, 2011 ; Motamedi et al, 2014 ). It has been demonstrated that air can be found in hip (Fairbairn et al, 1995 ; Liu et al, 2015 ; Schröder et al, 2016 ), shoulder (Ito et al, 2008 ; Jordanov and Block, 2010 ), sternoclavicular (Ito et al, 2008 ), metacarpophalangeal (Malghem et al, 2011 ), temporomandibular (Moncada et al, 2008 ), and knee joints (Jordanov and Block, 2010 ) and in degenerative intervertebral discs (Stallenberg et al, 2001 ; D'Anastasi et al, 2011 ; Feng et al, 2011 ; Wadhwa et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fick was the first to identify the vacuum phenomenon on radiographic images (Fick, 1919 ). Since then it has been demonstrated that computed tomography (CT) has a higher sensitivity than radiography and magnetic resonance imaging (MRI) for evaluating the presence of intra-articular air in large joints and vertebral discs (Ito et al, 2008 ; Moncada et al, 2008 ; Jordanov and Block, 2010 ; D'Anastasi et al, 2011 ; Motamedi et al, 2014 ; Wadhwa et al, 2016 ), while radiography and ultrasonography are more sensitive than CT and MRI for evaluating the presence of air in small joints (Malghem et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%